(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Budianto BH, Sasongko ND. 2022. Composition and abundance level of pest mites in jasmine gambier (Jasminum officinale) plantation of Purbalingga, Central Java, Indonesia affected by some abiotic factors. Biodiversitas 23: 5227-5232. The decline in productivity of gambier jasmine flowers is not only caused by the reduction of gambier jasmine land area but also insect, caterpillar and pest mite attacks. Types of pest mites and their population dynamics are closely related to abiotic factor conditions such as temperature, humidity, rainfall, season, an abundance of predatory mites and types of plant cultivars. The study aimed to determine the types of pest mites and some abiotic factors that affect their abundance in gambier jasmine plants. The research method was a survey with a purposive sampling technique. Sampling locations were in Cipawon village, Bukateja sub-district, Purbalingga district, and Central Java Province, Indonesia. The obtained data were analyzed by analysis of variance at an error rate of 0.05. The types of pest mites that were identified consisted of 8 species, namely Brevipalpus phoenicis, B. californicus, B. papayensis, B. obovatus, Tetranychus urticae, T. kanzawai, T. cinnabarinus and Tyrophagus putrescentiae. The type of pest mite always found at each sampling point was B. phoenicis, with an abundance range of 0.027 to 0.067. The results of the analysis of the variance of pest mite abundance in gambier jasmine plantations showed that abundance of individuals between pest mite species did not significantly differ at all sampling points. Based on multivariate analysis, it was noted that trichome density had the most influence on pest mite abundance with a population model of Y = 0.399 + 0.043a + 0.012b.